Wild Edible Plant Bio-diversity and Utilization System in Nech Sar National Park, Ethiopia - kebebew, Mulugeta; Leta, Gemechu (International Journal of Bio-resource and Stress Management, 2023)
Nech Sar National Park is one of the wildlife conservation areas of Ethiopia. The park is a very scenic and accessible. Wild edible plant biodiversity and utilization system was investigated in Nech Sar National Park from June 1, 2014 to May 30, 2015. A total of 60 informants between the ages of 20 and 80 were identified using prior information. Data were collected using semi-structured interviews, guided field walk, discussions, market surveys and field observation. A total of 51 wild edible species were identified by members of the local communities. Of these, 10 species were reported only by the Gamo community, eight by the Koera community, and seven by the Gujji community; while the remaining 26 were reported by three of them. Preference ranking indicated that the fruits of Moringa stenopetala are the most preferred edible plant by the local communities. The local people access the National Park for some of the wild edible plants as they are largely depleted from the surrounding areas. The yet untapped potentials of the wild edible plants as food sources in the area need better attention in future research plans. The poor communication system, on the other hand, has hindered the knowledge transfer from elders to youngsters and among different genders. The issue of conservation of wild edible plants is unquestionable to ensure household food security, dietary diversification and local communities’ income, which also contributes to the bio-diversity.